Postdoc Identity, Jurisdictional Issues, Ideologies, and Unions: Considerations in Organizing Professionals. (June 2023) - Rhoades, Gary
This study of U.S. postdocs and unions analyzes the public discourse of national entities, a national postdoc advocacy group, and of local postdoc unions and their collective bargaining agreements. The analytical focus and findings address: (a) postdocs' identity as "professors-in-training" or exploited employees; (b) the professional jurisdictional issues and due process rights identified as problematic and on which postdocs' bargaining is focused; and (c) broader ideologies and social justice issues that characterize postdocs' working conditions and that inform their mobilizing. The findings offer insights into organizing professionals in a time when their status/work is being degraded.